Temperament and Offending Behaviors in Male Adolescents - Manetsch, Madleina (International journal of offender therapy and comparative criminology, 2024)
The aim of the current paper was to examine temperament profiles and temperament dimensions as risk factors for persistent criminal behavior in juveniles who offended (JOs). A sample of 137 male adolescents from a Swiss detention center and 137 age and sex matched community controls were included in the present study. Temperament was measured with the Junior Temperament and Character Inventory (JTCI). Using Latent Profile Analysis (LPA), three temperament profiles were found, a “moderate,” an “adventurous-disinhibited” (higher levels of novelty seeking, lower levels of harm avoidance, reward dependence, and persistence), and a “worried-passive” profile (higher levels of harm avoidance, low persistence). None of the profiles and dimensions were associated with detention sample (i.e., JO) status. In JOs, the “novelty seeking” scale predicted recidivism after release from detention even when controlling for other covariates. Further research should address temperament profiles and temperament dimensions in larger samples of JOs to elaborate their relation to previous and future offending behavior.